Searching for ZZ Ceti white dwarfs in the Gaia survey. Issue Volume 15:Issue S357(2019) (October 2019) - Vincent, Olivier; Bergeron, Pierre; Lafrenière, David
Abstract: The Gaia satellite recently released parallax measurements for nearly 400, 000 white dwarf stars, allowing for precise measurements of their physical parameters. By combining these parallaxes with Pan-STARRS and CFIS-u photometry, we measured the effective temperatures and surface gravities for all white dwarfs within 100 pc and identified a sample of ZZ Ceti white dwarf candidates within the instability strip. We report the results of a photometric follow-up, currently under way, aimed at identifying new ZZ Ceti stars among this sample using the PESTO camera attached to the 1.6-m telescope at the Mont Mégantic Observatory. Our goal is to verify that ZZ Ceti stars occupy a region in the logg - T eff plane where no nonvariable stars are found, supporting the idea that ZZ Ceti pulsators represent a phase through which all hydrogen-line (DA) white dwarfs must evolve.